STAT1-Dependent Signal Integration between IFNγ and TLR4 in Vascular Cells Reflect Pro-Atherogenic Responses in Human Atherosclerosis - Chmielewski, Stefan (PLoS One, 2014)
Signal integration between IFNγ and TLRs in immune cells has been associated with the host defense against pathogens and injury, with a predominant role of STAT1. We hypothesize that STAT1-dependent transcriptional changes in vascular cells involved in cross-talk between IFNγ and TLR4, reflect pro-atherogenic responses in human atherosclerosis. Genome-wide investigation identified a set of STAT1-dependent genes that were synergistically affected by interactions between IFNγ and TLR4 in VSMCs. These included the chemokines Cxcl9, Ccl12, Ccl8, Ccrl2, Cxcl10 and Ccl5, adhesion molecules Cd40, Cd74, and antiviral and antibacterial genes Rsad2, Mx1, Oasl1, Gbp5, Nos2, Batf2 and Tnfrsf11a. Among the amplified genes was also Irf8, of which Ccl5 was subsequently identified as a new pro-inflammatory target in VSMCs and ECs. Promoter analysis predicted transcriptional cooperation between STAT1, IRF1, IRF8 and NFκB, with the novel role of IRF8 providing an additional layer to the overall complexity. The synergistic interactions between IFNγ and TLR4 also resulted in increased T-cell migration and impaired aortic contractility in a STAT1-dependent manner. Expression of the chemokines CXCL9 and CXCL10 correlated with STAT1 phosphorylation in vascular cells in plaques from human carotid arteries. Moreover, using data mining of human plaque transcriptomes, expression of a selection of these STAT1-dependent pro-atherogenic genes was found to be increased in coronary artery disease (CAD) and carotid atherosclerosis. Our study provides evidence to suggest that in ECs and VSMCs STAT1 orchestrates a platform for cross-talk between IFNγ and TLR4, and identifies a STAT1-dependent gene signature that reflects a pro-atherogenic state in human atherosclerosis.